A hazai felsőoktatásban részt vevő határon túli magyar hallgatók munkaerőpiaci elképzelései - Csehné Papp, Imola (Közép-Európai Közlemények, 2012)
The paper discusses the opinion and ideas of minority Hungarian students living beyond the borders of Hungary. They form one of the segments of students studying within Hungarian higher education, starting their career in the near future. The objective of the questionnaire survey is to explore the intent and thoughts of Hungarian students living beyond Hungarian borders but studying in Hungary: why they study in higher education, how they see their labour market positions and job opportunities in the future, whether they see the true picture of the Hungarian labour market, what plans they have. The research is based on the hypothesis that studying and work represent an outstanding value for the students coming from beyond the borders to the mother country, therefore they make a profit from it and feel safe in Hungary. Most of them does not use Hungary as only a step towards some European Union or other country but they expect their future in Hungary. Another hypothesis is that the minority Hungarian students beyond Hungary have relatively true picture and knowledge about the possibilities offered by the Hungarian labour market. While the first hypothesis was proved to be completely true, the second was confirmed only partly.